DIGITAL BRANDING IN THE CONTEXT OF GLOBALIZATION - TERENTIEVA, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In the article, the author analyzes the main factors and stages of forming effective digital branding strategies, taking into account innovations in marketing, the latest technologies, and audience preferences. The features and elements of a digital brand are studied, which help create a recognizable and sustainable online identity. The importance of interacting with end consumers through digital channels is analyzed, determining how the accuracy and personalization of communications can improve mutual understanding with the audience and form a positive brand image.Special attention is also paid to creating a unique online brand identity, which allows it to stand out among competitors and build consumer loyalty. This includes the use of modern graphic elements, visual styles, content, and communication tools that best meet the needs and preferences of the target audience. In this context, it is also important to note that continuous improvement of brand elements, adaptation to new technological requirements and trends, allows companies to maintain competitiveness in a rapidly changing market.Among the external factors affecting the formation of a digital branding strategy, particular importance is attached to economic conditions, technological innovations, and changes in the regulatory environment. These factors significantly change the ways in which brands interact with their audience, creating both new opportunities and challenges for companies. Analyzing these changes allows brands to adjust their strategies to remain relevant and competitive.For successful competition in the global market, companies need to implement modern digital marketing tools, use the capabilities of big data and predictive analytics to identify new trends and respond promptly to changes in consumer preferences. Therefore, key aspects are not only adapting to technological innovations but also the ability to predict future changes in consumer preferences and behavior, which allows brands to stay ahead in their industry.
Keywords: factors and stages of forming an effective digital branding strategy; innovations in the field of marketing; audience; features of a digital brand; the latest technologies; elements of a digital brand; consumers; content; experience; brand identity; analytics; communication